WIWIK RUMIATI - admin, Keguru (KEGURU "Jurnal Ilmu Pendidikan Dasar", 2019)
Abstract This study aims to improve learning activities and students' problem-solving abilities on fraction topics by applying problembased learning models of learning. This research is a classroom action research by following the Kemmis & McTaggart model. This research was conducted at SDN 195 / V Pinang Merah, Jambi. The research subjects consisted of 6 fourth grade students. Data obtained from tests and observations. Based on the results of the analysis, it was found that student learning activities increased from 2.57% in first cycleto 4.43% in second cycle. In addition, the average score of students' problem-solving skills on the topic of fractions also increased from 21.21 in first cycle to 72.73 in second cycle.